Rare genetic variants confer a high risk of ADHD and implicate neuronal biology - Ditte Demontis; Jinjie Duan; Yu-Han H. Hsu; Greta Pintacuda; Jakob Grove; Trine Tollerup Nielsen; Janne Thirstrup; Makayla Martorana; Travis Botts; F. Kyle Satterstrom; Jonas Bybjerg-Grauholm; Jason H. Y. Tsai; et al. (Nature, 2026)
Abstract Attention deficit hyperactivity disorder (ADHD) is a childhood-onset neurodevelopmental disorder with a large genetic component 1 . It affects around 5% of children and 2.5% of adults 2 , and is associated with several severe outcomes 3–11 . Common genetic variants associated with the disorder have been identified 12,13 , but the role of rare variants in ADHD is mostly unknown. Here, by analysing rare coding variants in exome-sequencing data from 8,895 individuals with ADHD and 53,780 control individuals, we identify three genes ( MAP1A , ANO8 and ANK2 ; P < 3.07 × 10 −6 ; odds ratios 5.55–15.13) that are implicated in ADHD. The protein–protein interaction networks of these three genes were enriched for rare-variant risk genes of other neurodevelopmental disorders, and for genes involved in cytoskeleton organization, synapse function and RNA processing. Top associated rare-variant risk genes showed increased expression across pre- and postnatal brain developmental stages and in several neuronal cell types, including GABAergic (γ-aminobutyric-acid-producing) and dopaminergic neurons. Deleterious variants were associated with lower socioeconomic status and lower levels of education in individuals with ADHD, and a decrease of 2.25 intelligence quotient (IQ) points per rare deleterious variant in a sample of adults with ADHD ( n = 962). Individuals with ADHD and intellectual disability showed an increased load of rare variants overall, whereas other psychiatric comorbidities had an increased load only for specific gene sets associated with those comorbidities. This suggests that psychiatric comorbidity in ADHD is driven mainly by rare variants in specific genes, rather than by a general increased load across constrained genes.